![\frac{x^2-2x-24}{x^2-16}=\frac{(x-6)(x+4)}{(x-4)(x+4)}=\frac{x-6}{x-4} \frac{x^2-2x-24}{x^2-16}=\frac{(x-6)(x+4)}{(x-4)(x+4)}=\frac{x-6}{x-4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2-2x-24%7D%7Bx%5E2-16%7D%3D%5Cfrac%7B%28x-6%29%28x%2B4%29%7D%7B%28x-4%29%28x%2B4%29%7D%3D%5Cfrac%7Bx-6%7D%7Bx-4%7D)
..................................................................................................................................................................................................................................................................................................................................